Pro Zend Framework Techniques Build a Full CMS Project - Lyman, Forrest (Apress : Imprint: Apress, 2009)
The Zend Framework is a truly amazing PHP-based web application development framework and platform that is breathing new life into PHP development. One of the most common uses for a framework such as this is to build content-driven web sites. Pro Zend Framework Techniques offers: A structured guide for PHP developers, ultimately helping you to create more flexible software much more quickly Clear guidance through the entire process of building a custom content management system (CMS) with the Zend Framework The ideal example project, building a CMS, to illustrate how to use the many different aspects of the framework.